2003
DOI: 10.1086/375589
|View full text |Cite
|
Sign up to set email alerts
|

Internalization-Associated Proteins among Streptococcus pyogenes Isolated from Asymptomatic Carriers and Children with Pharyngitis

Abstract: Sixty-two strains of Streptococcus pyogenes isolated from 30 asymptomatic school children and 32 children with pharyngitis were characterized to analyze the involvement of 2 fibronectin-binding proteins (F/SfbI and PrtF2/PfbpI) in S. pyogenes colonizing asymptomatic carriers and to determine the possible association between these proteins and the genes associated with macrolide resistance. In this study, we demonstrated that the proportion of S. pyogenes strains carrying the pfbpI gene was significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
(16 reference statements)
1
12
0
Order By: Relevance
“…12 In the present study, the proportion of isolates carrying the prtF1 gene was higher among strains from noninvasive infections than among strains from invasive infections, although the prevalence of isolates with the prtF1 gene among strains from invasive infections varied between 50% and 65% in other studies. 3,6,8,10,[19][20][21] In contrast, the carriage rate of the prtF2 gene was comparable to the proportion generally reported in other studies. 10,[22][23][24] Isolates carrying the prtF1 and prtF2 genes simultaneously were more prevalent among strains from noninvasive infections than among strains from invasive infections.…”
Section: Discussionsupporting
confidence: 80%
“…12 In the present study, the proportion of isolates carrying the prtF1 gene was higher among strains from noninvasive infections than among strains from invasive infections, although the prevalence of isolates with the prtF1 gene among strains from invasive infections varied between 50% and 65% in other studies. 3,6,8,10,[19][20][21] In contrast, the carriage rate of the prtF2 gene was comparable to the proportion generally reported in other studies. 10,[22][23][24] Isolates carrying the prtF1 and prtF2 genes simultaneously were more prevalent among strains from noninvasive infections than among strains from invasive infections.…”
Section: Discussionsupporting
confidence: 80%
“…In particular, proteins of the series F have been demonstrated to have a role in the pathogenesis of group A streptococcal infections. The proportion of prtF1 gene reported in other studies varies greatly, ranging from more than 70 to 80% (11,25) to 30 to 40% (6,20,27). The only study examining strains from invasive infections (30) reported an extremely low incidence of prtF1 among isolates from invasive infections in Europe, limited to emm6 type isolates; however, we found that the forward primer they used was specific for emm6 and could not detect prtF1 sequences that differed in the specific segment in other emm types (data not shown).…”
Section: Discussionmentioning
confidence: 92%
“…Macrolide resistance mechanisms include target site modification, leading to resistance to macrolides, lincosamides, and streptogramin B (MLS phenotype), or an efflux mechanism mediating resistance only to 14-and 15-membered macrolides (M phenotype) (11). Recently, an association between erythromycin resistance and cell invasiveness, as demonstrated by the presence of the fibronectin binding protein F1, encoded by the prtF1 gene, has been observed (8,14). In addition, Cocuzza et al recently demonstrated selection for prtF1-positive strains after ␤-lactam therapy (5).…”
mentioning
confidence: 99%